Supporting Sustainable Energy Finance through Hierarchical Multi-criteria Sorting of Electricity Generation Technologies - Solares, Efrain; Díaz, Raymundo; Sanchez, Juan Manuel; Fernández, Eduardo; Granados Montelongo, Juan Antonio; Álvarez Gaona, Juan Antonio (International Journal of Energy Economics and Policy, 2026)
Sustainable finance requires decision-support tools capable of integrating financial indicators with environmental and social risk factors in a transparent and data-driven manner. This study introduces a hierarchical multi-criteria sorting approach for the evaluation of electricity generation technologies, aimed at informing capital allocation and investment screening decisions. The framework relies exclusively on quantitative criteria obtained from public datasets and organizes them into a structured hierarchy encompassing economic performance, technical reliability, system relevance, and environmental and health impacts. Interval-valued evaluations and preference parameters are employed to represent uncertainty and heterogeneity in financial decision contexts. The resulting range-based classifications distinguish technologies according to their overall acceptability from a sustainable finance perspective. Results for the U.S. electricity sector highlight the ability of the approach to support responsible investment decisions under multiple, potentially conflicting financial and sustainability considerations.